A Nuyorican Absurdist: Pedro Pietri and His Plays of Happy Subversion - Crespy, David (Latin American Theatre Review, 2012)
Jerzy Grotowski once wrote of the visionary Antonin Artaud, “He wasn’t entirely himself;” the same might be said of the late poet Pedro Pietri—who wasn’t entirely himself since he began writing plays. Pietri’s plays, having been produced in New York since the late sixties, are an example of the wave of Nuyorican theatre in the US prominent at that time— characterized by experimentation in form and the merging of social issues within that form. While others have explored Pietri’s work in tandem with his poetry, the phenomenological approach taken in this essay focuses on his plays and brackets off other concerns, getting at the “thingness” and texture of Pietri’s bizarre farcical dramaturgy, particularly within the context of how it compares to European absurdist technique.